1987
DOI: 10.1111/j.1346-8138.1987.tb02997.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Psoriasis Vulgaris with Oral 1α,25‐Dihydroxyvitamin D3

Abstract: Psoriasis is a common inflammatory skin disease, but its pathogenesis is unknown. This paper presents 2 cases of psoriasis vulgaris in which the skin lesions were improved for 3 months and more after the start of oral treatment with 1α,25‐dihydroxyvitamin D3 at a dose of 0.5 μg/day. The circulating levels of calcium, inorganic phosphate, 25‐hydroxyvitamin D, 1α,25‐dihydroxyvitamin D, parathyroid hormone and calcitonin were within normal ranges before and after the start of treatment. These findings suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The reason for the exclusion of oral vitamin D as a recommended treatment for psoriasis by both the NPF and AAD is unclear. Four different forms of oral vitamin D have been shown to be safe treatments for psoriasis dating back to the 1930s [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], when oral vitamin D 2 was first found to be effective in treating a number of diseases in addition to psoriasis, including asthma [ 29 ], rheumatoid arthritis [ 30 , 31 ], rickets [ 32 ] and tuberculosis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Sunshine, UVB phototherapy and cod liver oil, a concentrated food source of vitamin D, were also noted to be effective treatments for psoriasis [ 12 , 40 , 41 , 42 , 43 , 44 ], rickets [ 45 , 46 ] and TB [ 39 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] during that era.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the exclusion of oral vitamin D as a recommended treatment for psoriasis by both the NPF and AAD is unclear. Four different forms of oral vitamin D have been shown to be safe treatments for psoriasis dating back to the 1930s [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], when oral vitamin D 2 was first found to be effective in treating a number of diseases in addition to psoriasis, including asthma [ 29 ], rheumatoid arthritis [ 30 , 31 ], rickets [ 32 ] and tuberculosis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Sunshine, UVB phototherapy and cod liver oil, a concentrated food source of vitamin D, were also noted to be effective treatments for psoriasis [ 12 , 40 , 41 , 42 , 43 , 44 ], rickets [ 45 , 46 ] and TB [ 39 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] during that era.…”
Section: Introductionmentioning
confidence: 99%
“…The central role of the VDR in regulation of different molecular pathways (including immune mechanisms) made 1,25(OH) 2 D 3 and its analogues therapeutically promising for a wide spectrum of clinical applications. Proof‐of‐concept of systemically applied vitamin D 3 in treating psoriasis patients has been demonstrated in clinical trials (20,21). Clinical use of 1,25(OH) 2 D 3 , however, in psoriasis and other (auto‐) immune diseases as a systemically applied immunomodulator is not suited because of its prominent calcium‐mobilizing effect that can lead to severe organ calcifications, bone resorption and organ failure (22–24).…”
Section: Introductionmentioning
confidence: 99%
“…During the study, it was observed that a single dose at bedtime, rather than twice daily, helped to minimize the hypercalciuria. Of the 14 patients, ten showed a "significant clearing," whereas 4 patients had no benefit or only mild clinical response [135]. showed at least moderate improvement for 7 of 10 patients.…”
Section: Vitamin Dmentioning
confidence: 98%